Identification of a gene from Neurospora crassa with similarity to a glucoamylase gene from Schwanniomyces occidentalis - Daniel J. Ebbole; Lea Madi (Fungal Genetics Reports, 1996)
Glucoamylases are important industrial enzymes used in the conversion of starches to syrups and in other fermentation processes. Previously, the gene encoding the major glucoamylase activity of N. crassa was characterized (Stone et al. 1993 Curr. Genet 24:205-211). Here we report the identification of a possible second glucoamylase (gla-2) that is similar to a member of a class of glucoamylases represented by the GAM1gene of S. occidentalis (Dohmen et al. 1990 Gene 95:111-121).